Reproductive Biology of Oci Fish Selaroides leptolepis in Tomini Bay - Pasisingi, Nuralim; Ibrahim, Putri Sapira; Moo, Zulkifli Arsalam; Tuli, Munirah (977-2407769)
Local people name Selaroides leptolepis distributed in Tomini Bay as Oci Fish. A study of the fish reproductive biology, which is one aspect of fisheries biology, is crucial to support the implementation of sustainable Oci Fish resource management policies. This study aims to determine the average length at first maturity, gonad maturity stages, and fecundity of the fish in Tomini Bay. Sampling was carried out using a stratified random sampling method from the catches of the fishermen landed in Fish Landing Base Kampung Tenda, Gorontalo City. The time interval sampling was conducted per month during April, May, and June 2020. Fish and egg samples preserved using ice cubes and a 10% formaldehyde solution correspondingly. The results of the study showed that the Oci Fish in Tomini Bay had a length range of the first maturity between 166 and 174 mm with a gonad maturity index ranging from 1.773 to 2.760%. The average fish fecundity was 16623 Â± 4850 eggs.